Conversion of Human Fibroblasts Into Monocyte-Like Progenitor Cells. (14th October 2014) - Pulecio, Julian; Nivet, Emmanuel; Sancho-Martinez, Ignacio; Vitaloni, Marianna; Guenechea, Guillermo; Xia, Yun; Kurian, Leo; Dubova, Ilir; Bueren, Juan; Laricchia-Robbio, Leopoldo; Belmonte, Juan Carlos Izpisua
Abstract : Reprogramming technologies have emerged as a promising approach for future regenerative medicine. Here, we report on the establishment of a novel methodology allowing for the conversion of human fibroblasts into hematopoietic progenitor-like cells with macrophage differentiation potential. SOX2 overexpression in human fibroblasts, a gene found to be upregulated during hematopoietic reconstitution in mice, induced the rapid appearance of CD34+ cells with a concomitant upregulation of mesoderm-related markers. Profiling of cord blood hematopoietic progenitor cell populations identified miR-125b as a factor facilitating commitment of SOX2 -generated CD34+ cells to immature hematopoietic-like progenitor cells with grafting potential. Further differentiation toward the monocytic lineage resulted in the appearance of CD14+ cells with functional phagocytic capacity. In vivo transplantation of SOX2/ miR-125b-generated CD34+ cells facilitated the maturation of the engrafted cells toward CD45+ cells and ultimately the monocytic/macrophage lineage. Altogether, our results indicate that strategies combining lineage conversion and further lineage specification by in vivo or in vitro approaches could help to circumvent long-standing obstacles for the reprogramming of human cells into hematopoietic cells with clinical potential. Stem Cells 2014;32:2923–2938